The role of some chemical transactions in the germination of seeds of some salt-stressed pepper genotypes - Hussein, Zobaeda Ali; Sofan, Nedal Jamil; Al Atalah, Bassam Fahad (Journal of agricultural, environmental and veterinary sciences, 2021)
This research was carried out at Sweida Research Center/ General commission for Scientific Agricultural Research/ Syria during 2020. Seven pepper genotypes were used; five local varieties (10496, 10743, Aleppo pepper, thick sweet pepper and deer horn pepper) and two lines (129 and 110). This research aimed to determining the effect of seed priming treatments in enhancing the tolerance of pepper to salt stress during germination stage. Seeds were divided into four groups, the first group was treated with distilled water, the second with NaCl (50 mM), the third with poly ethylene glycol 6000 (PEG) (16.7 mM) and the fourth with sorbitol (250mM). Seeds were exposed after drying to several NaCl levels (0, 2, 4, 6 gl-1), in addition to untreated control for each genotype. Germination percentage, vigor and speed indicators were recorded. The research was conducted according to a completely random design, and data were analyzed by two way ANOVA at 0.01 significant level. In this research, studied genotypes showed different behavior according to the treatments and salinity levels. The results indicated that the treatments of PEG and sorbitol were superior for the studied indicators in most genotypes, especially at the low levels of salinity. In addition, the salinity and water treatments for most genotypes did not cause an increase in the values ​​of the studied indicators. Depending on these results, it is advisable to treat pepper seeds before sowing with sorbitol or PEG when the salinity level is low.